Genealogia do curso superior de música da Universidade de Uberlândia, MG (1957–69) - Silva, Ruth de Sousa Ferreira (2021)
This thesis presents a study on the music course at the University of Uberlândia city. It was designed to understand how this course was included in the political and academic movement to organize a local university. This understanding was pursued by taking it account the following aim: to analyze the genealogy of the higher education in music and the importance of conservatories as higher education institutions until their inclusion in public universities, which are recurring facts in the officialization of university music education. The research relied upon postulates of historical and dialectical materialism, especially links between the local, the regional, and the national. The research covered a period going from 1957 — the year of the opening of Uberlândia conservatory as a private institution that offered a higher education degree) — to 1969 — when Uberlândia’s University brought together isolated higher education courses in the city. Research sources included iconography, press, correspondence, cartulary records, call minutes, conservatory exam shits; and others. By the critical reading of such documentation in dialogue with theoretical and conceptual references, school institutions, higher education of music, political movement, modernization, and social transformation emerged as categories of analysis, The study confirms its hypothesis: Cora Pavan Capparelli had a political influence that gave her more means to turn the conservatory music course into an arts college. For this, she had the support of local politicians and authorities. The result of her commitment was, for example, the graduation of many students in Music. This study shows that the process of creating and recognizing music courses and the creation of an Arts college were part of a political project derived from public policies to found a (public) university in Uberlândia. The music degree gained visibility and had its recognition in the military rule, which used strategies and political influence to create universities and recognize higher education courses in isolated institutions.